Pearls and pitfalls of bile duct injury during laparoscopic cholecystectomy: A case report of the importance of preoperative detection of situs inversus totalis - Afifudin, Muhammad; Meindhani, Tety Ratna; Danardono, Edwin (Edelweiss Applied Science and Technology, 2025)
Situs inversus totalis is a rare congenital condition characterized by mirror-image organ transposition, which complicates laparoscopic cholecystectomy due to reversed anatomy. This case report highlights the importance of recognizing situs inversus totalis before surgery to prevent pitfalls. It discusses the surgical management of a patient with situs inversus undergoing cholecystectomy for cholelithiasis, addressing the procedural adaptations required and the resulting clinical outcomes. A 48-year-old woman with cholelithiasis, without cholecystitis, presented with recurrent right upper abdominal pain. Imaging confirmed gallstones, and laparoscopic cholecystectomy was planned. Intraoperatively, situs inversus totalis was discovered, complicating the procedure. A bile duct injury occurred, necessitating conversion to open surgery with hepaticojejunostomy. Postoperatively, the patient recovered uneventfully, with no complications. Situs inversus totalis complicates surgeries like laparoscopic cholecystectomy due to reversed organ positioning. Failure to recognize it preoperatively can lead to complications, such as bile duct injury. Proper imaging, surgical adaptation, and intraoperative cholangiography are crucial for successful outcomes in patients with such anatomical variations.